Working Paper 27: The Double Challenge of Market and Social Incorporation: Progress and Bottlenecks in Latin America - Martínez Franzoni, Juliana (2012)
Latin American countries have historically failed to secure market incorporation (e.g. people’s participation in the cash nexus, which in turn requires the creation of a sufficient number of formal well-paying jobs) and social incorporation (e.g. decommodification of rights) simultaneously. High structural heterogeneity in production and weak fiscal capacity resulted in dual social systems and extended and informal labor market. Has this changed in recent years? This paper draws on the experience of Bolivia, Brazil, Chile, Peru and Uruguay to answer this question. We distinguish between short term outcomes – which may depend on benign international conditions –and policy changes which are more important for long term success. Our analysis highlights Brazil and Uruguay’s unique success overall and also shows that all countries have done better in terms of social than market incorporation. We also discuss some of the challenges to secure further improvements in market and social incorporation in the immediate future, including competition from China and low state capacity.